Comparing different preparations and doses of rosehip powder in patients with osteoarthritis of the knee: an exploratory randomized active-controlled trial. (June 2014) - Christensen, Robin; Tarp, Simon; Altman, Roy D; Henriksen, Marius; Bartels, Else M; Klokker, Louise; Boesen, Mikael; Furst, Daniel E; Holm, Christian C; Danneskiold-Samsøe, Bente; Bliddal, Henning
Aim: We compared original rosehip powder consisting of whole rosehips including seeds, with two different doses of a novel enhanced rosehip powder of rosehips without their seeds, for patients with knee osteoarthritis (OA).Methods: A total of 150 patients with symptomatic knee OA were randomly assigned to original powder (six capsules/day), enhanced powder (six capsules/day) or enhanced powder (three capsules/day). The primary outcome was change from baseline in the Knee Injury and Osteoarthritis Outcome Score (KOOS) item, 'pain during walking on flat surface', assessed after 12 weeks. Statistical analyses were based on the intention-to-treat population.Results: During the trial period the change in the primary outcome was comparable across groups. Changes in the KOOS symptoms supported a potential superiority of enhanced powder versus original powder, with a difference of 5.97 KOOS points (95% CI: 0.92–11.02; p = 0.02).Conclusion: Enhanced rosehip powder is at least as good, even taken as three capsules/day, as the original rosehip product for patients with symptomatic OA.